Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0165733
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Gas Exchange and Fluorescence of Two Winter Wheat Varieties in Response to Drought Stress and Nitrogen Supply

Abstract: Water and nitrogen supply are the two primary factors limiting productivity of wheat (Triticum aestivum L.). In our study, two winter wheat varieties, Xinong 979 and large-spike wheat, were evaluated for their physiological responses to different levels of nitrogen and water status during their seedling stage grown in a phytotron. Our results indicated that drought stress greatly reduced the net photosynthetic rate (Pn), transpiration rate (E), and stomatal conductance (Gs), but with a greater increase in inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 49 publications
12
58
1
Order By: Relevance
“…After 10-15 days of no water supply, the maize leaves at 120, 180, 240, and 260 kg N ha −1 treatment rates gradually began to curl from 10:00 a.m. to 5:00 p.m. daily, and the leaves were unfurled for the rest time of the day (Figure 2a). Several studies have shown that N deficiency exacerbated the sensitivity of stomata to drought [15,26]; however, we did not observe the leaf curling in the absence of N treatments, which was found under higher N treatment rates. This might be the case, as the application of N fertilizers increased plant water transpiration ( Figure 5), causing the plants treated with higher N treatment rates to enter the drought state earlier, which masked the increased resistance to drought stress with additional N treatments for the maize.…”
Section: N Use Efficiencycontrasting
confidence: 99%
See 1 more Smart Citation
“…After 10-15 days of no water supply, the maize leaves at 120, 180, 240, and 260 kg N ha −1 treatment rates gradually began to curl from 10:00 a.m. to 5:00 p.m. daily, and the leaves were unfurled for the rest time of the day (Figure 2a). Several studies have shown that N deficiency exacerbated the sensitivity of stomata to drought [15,26]; however, we did not observe the leaf curling in the absence of N treatments, which was found under higher N treatment rates. This might be the case, as the application of N fertilizers increased plant water transpiration ( Figure 5), causing the plants treated with higher N treatment rates to enter the drought state earlier, which masked the increased resistance to drought stress with additional N treatments for the maize.…”
Section: N Use Efficiencycontrasting
confidence: 99%
“…Since nitrogen (N) is a vital component required for the synthesis of chlorophyll and photosynthetic enzymes in plants, which directly and indirectly impact the photosynthesis of crops, its presence or absence can determine the overall yields of crops [14]. Drought stress strongly affects growth and N metabolism, while the application of N can contribute to drought resistance to a certain extent in many plants [15]. Under water deficits, N supplies can be conducive toward the enhancement of the drought resistance of crops by protecting photosynthetic apparatus, activating antioxidant defense systems and improving osmoregulation [16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, WUEi slightly (not significant) or WUE significantly (during morning measurement period) increased under terminal drought (Figure 2i, 2j, 2k and 2l), due to faster decrease in gs and E compared to A. Similar increase in WUE and WUEi under drought stress were reported for wheat seedlings (WANG et al, 2016). The flag leaf is the major source of assimilates for grain-filling (LARBI, 2004), therefore stay-green strategy which combines delaying senescence, maintaining leaf chlorophyll content, sustaining transpiration, and photosynthetic rate (VADEZ et al, 2011) represents one of the key factors that contributes to embodiment of yield potential under terminal drought stress.…”
supporting
confidence: 70%
“…The CO 2 assimilation rate decreased by 41.06% when compared to plants growth with 100% and 20% of field capacity (Figure 3a). The effects of reducing water availability on the photosynthetic rate were reported in several studies (Rahmati et al, 2015;X. Wang, L. Wang, & Shangguan, 2016;Pazzagli, Weiner, & Liu, 2016).…”
Section: Leaf Gas Exchangementioning
confidence: 99%